2005
DOI: 10.1186/1477-7800-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative core biopsy accurate in determining the hormone receptor status in women with invasive breast cancer?

Abstract: BackgroundThe objective of this study was to determine the concordance rate between core needle biopsy (CNB) and surgical excision of invasive breast cancer regarding the oestrogen receptor (ER) and Progesterone receptor (PgR) status as determined by Immunohistochemistry (IHC).MethodsHormone receptor status was established using IHC (using quickscore system 0–8) on preoperative CNB and subsequent surgical excision in 93 patients with invasive breast cancer. Results were compared taking into account tumour's si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Nevertheless, a greater distribution and bigger change of proportion score from both two biopsy specimens to surgical excisions were noted for PgR than ER ( Figures 3A, B ). These findings above are consistent with previous studies which may be due to the reason that PgR is more heterogeneously distributed ( 26 , 35 , 36 ). Identifying HER2-positive breast malignant tumor patients prior to surgery is important since neoadjuvant or postoperative adjuvant HER2-targeted therapy is an effective option for these patients.…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, a greater distribution and bigger change of proportion score from both two biopsy specimens to surgical excisions were noted for PgR than ER ( Figures 3A, B ). These findings above are consistent with previous studies which may be due to the reason that PgR is more heterogeneously distributed ( 26 , 35 , 36 ). Identifying HER2-positive breast malignant tumor patients prior to surgery is important since neoadjuvant or postoperative adjuvant HER2-targeted therapy is an effective option for these patients.…”
Section: Discussionsupporting
confidence: 93%
“…However, immunohistochemistry (IHC) assessment in CNB samples may be less reliable than in surgical specimens' due to the relatively smaller sample size and tumor heterogeneity [ 3 4 ]. Several studies have reported the concordance between preoperative CNB and surgical specimens for estrogen receptor (ER), and human epidermal growth factor receptor 2 (HER2) determination [ 5 6 7 ]. A recent meta-analysis has shown that the CNB tissue could replace open excision biopsy for determining ER, progesterone receptor (PR), and HER2 status [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Valuable prognostic information is provided by the ER, PR, HER2 Neu and Ki-67 status of these samples and thus the response of the tumor to neoadjuvant and adjuvant chemotherapy can be predicted. [9] The CNB specimen may be the only available pretreatment tissue sample for assays of prognostic and predictive markers in some breast cancer patients, chiefly those patients who have been treated earlier with preoperative chemotherapy or neoadjuvant endocrine therapy. Cytotoxic chemotherapy may cause adequate tumor regression which can alter the histological, hormonal and proliferative markers.…”
Section: Introductionmentioning
confidence: 99%